Realization Strategy for BOTRAM : Identifying Critical Success Factors in Bekasi Inovation - febriantin, kariena (Kemudi, 2025)
This research aims to identify the factors that contribute to the effectiveness of public service innovation within the BOTRAM (Collaborate to Serve) program at the Bekasi Regency Population and Civil Registration Office. The analysis is based on Doley's theory, which includes various indicators such as leadership, strategy, performance, empowerment, group dynamics, innovation, learning, and communication that align with the factors facilitating successful service innovation. The key question guiding this research is: What factors influence the effectiveness of public service innovation in the BOTRAM (Collaborate to Serve) initiative at the Bekasi Regency Population and Civil Registration Office? This study employs a qualitative research approach. It features primary respondents from the Bekasi Regency Population and Civil Registration Office as well as residents of Bekasi Regency who utilize the services. Data for this study is gathered through interviews and direct observations as primary sources, while secondary data is obtained from documentation and other relevant materials. The analysis findings indicate that public service innovation via BOTRAM (Collaborate to Serve) has been largely successful, though not to its fullest potential. Challenges persist, particularly with some individuals lacking a complete understanding of service time standards and community engagement not reaching desired levels.